Dancing for Dollars and Paying for Love The Relationships between Exotic Dancers and their Regulars - Egan, D. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
This book takes an in-depth look at the relationships exotic dancers have with their regular customers, and explores the limits of using feminist theory to discuss sex work. This is an accessible, revealing, and new look at a perennially intriguing and divisive subject - ideal teaching material for undergraduate courses in a variety of fields.